Clinical and genetic characteristics of the patients with hypertension and hypokalemia carrying a novel SCNN1A mutation. (1st December 2022) - Chen, Mengzi; Lv, Xi; Li, Jiwu; Guo, Manli; Ma, Shaogang
Abstract: The objective of this study was to clinically and genetically characterize a pedigree with Liddle syndrome (LS). A LS pedigree comprising with one proband and seven family members was enrolled. The subjects' symptoms, laboratory results and genotypes were analyzed. Peripheral venous samples were collected from the subjects, and genomic DNA was extracted. DNA library construction and exome capture were performed on an Illumina HiSeq 4000 platform. The selected variant sites were validated using Sanger sequencing. The mutation effects were investigated using prediction tools. The proband and her paternal male family members had mild hypertension, hypokalemia and muscle weakness, including the absence of low renin and low aldosterone. Genetic analysis revealed that the proband carried a compound heterozygous mutation in SCNN1A, a novel heterozygous mutation, c.1130T > G (p.Ile377Ser) and a previously characterized polymorphism, c.1987A > G (p.Thr633Ala). The novel mutation site was inherited in an autosomal dominant manner and was predicted by in silico tools to exert a damaging effect. Alterations in the SCNN1A domain were also predicted by protein structure modeling. After six months of follow-up, treatment had significantly improved the patient's limb weakness and electrolyte levels. The novel mutation c.1130T > G of the SCNN1A gene was detected in the pedigree with LS. The clinical manifestations of the pedigree were described, which expand the phenotypic spectrum of LS. This result of this study also emphasizes the value of genetic testing for diagnosing LS.